POLITENESS STRATEGIES IN DAVE PELZER’S A CHILD CALLED IT - Sastri Damai Sarumaha; Suryani Siringo-ringo; Andi Jaihutan Silitonga (JURNAL LITTERA: FAKULTAS SASTRA DARMA AGUNG, 2020)
This study deals with Politeness Strategies in Dave Pelzer’s A Child Called It. The objectives of the study were (1)to find out the types of politeness strategies, (2) the most dominant type of politeness strategies, and (3) the reasons for the most dominant type of politeness strategies in Dave Pelzer’s A Child Called It. The result of the analysis showed (1) there were two types of politeness strategies in Dave Pelzer's A Child Called It, They were positive and negative politeness strategies. (2) The most dominant type of politeness strategy is negative politeness. (3) The reasons for the most dominant type of politeness strategies because people in the novel A Child Called It unappreciated and unsocialized one each other and prefer to used rude words that make the hearer hurt.